TORSION OF PRISMATIC CORE WITH LONGITUDINAL CRACS - Чумаченко, Ярослав Віталійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The paper presents a solution of the torsion problem for a rectangular prismatic bar with arbitrarily oriented longitudinal cracks. The stress function is found in the form of a sum of harmonic functions and a particular solution of the Poisson equation. Each component of the sum is associated with an individual segment of the boundary and is represented by a cosine development written in the respective local elliptic coordinates. The calculated values of the torsional rigidity and the tangential stress are given for several particular configurations.